Never Swim Alone and This Is a Play : 2nd Edition. - MacIvor, Daniel (Playwrights Canada Press, 2016)
Described by Carol Bolt as ""a world full of poetry and ceremony and mystery, where questions can be asked if not answered, "" Never Swim Alone and This Is A Play are two of Daniel MacIvor's most enduring plays.